PIEZO2 expression is an independent biomarker prognostic for gastric cancer and represents a potential therapeutic target - Yun-Chao Zhang; Min Yang; Cen-di Lu; Quan-Yao Li; Jin-na Shi; Jun Shi (Scientific Reports, 2024)
Abstract Gastric cancer (GC) is one of the most prevalent malignant tumors of the gastrointestinal system in the globe. The effect of PIEZO2 on the immune function and pathological features of gastric cancer remains to be explored. The Online database of cancer genes and GSE54129 have been used to analyze the clinical characteristics of PIEZO2 expression. We looked at the relationship between PIEZO2 and the immune systems of GC patients. The TIDE algorithm was used to explore the value of PIEZO2 in immunotherapy. Investigated the enrichment of PIEZO2 gene ontology and associated signal pathways using Online gene databases. The results show that overexpression of PIEZO2 was identified as an independent risk factor for patients with GC who had poor overall survival. Individuals may have a better prognosis if they had poorly differentiated GC and increased PIEZO2 expression (P < 0.05). We demonstrated a strong correlation between PIEZO2 and immune cells. The majority of immune checkpoint and immunological-related genes were associated with PIEZO2 expression. And PIEZO2 might be used as an immunotherapy target. Finally, the differential PIEZO2 genes in GC were mostly implicated in the processes of inflammation, immunological response, and tumor metastasis, according to functional analysis. PIEZO2 has a negative correlation with cell stemness and mutation levels in patients with GC and a positive correlation with immune cell infiltration and gene expression in the tumor microenvironment. These findings point to PIEZO2 as a potential new immunotherapy target of GC.